2013
DOI: 10.1098/rsbl.2013.0797
|View full text |Cite
|
Sign up to set email alerts
|

The impact of simulated chronic nitrogen deposition on the biomass and N 2 -fixation activity of two boreal feather moss–cyanobacteria associations

Abstract: Bryophytes achieve substantial biomass and play several key functional roles in boreal forests that can influence how carbon (C) and nitrogen (N) cycling respond to atmospheric deposition of reactive nitrogen (N r ). They associate with cyanobacteria that fix atmospheric N 2 , and downregulation of this process may offset anthropogenic N r inputs to boreal systems. Bryophytes also promote soil C accumulation by thermally insulating soils, and changes in their biomass influence soil C dynamics. Using a unique l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…Furthermore, we found that symbiotic N fixation was less sensitive to N inputs than was free-living N fixation, as evidenced by the smaller response ratios of BNF in nodule (15.2%) compared to those in soil, litter, moss, and lichen (21.2%-74.1%; Figure 2b). Given that there are more symbiotic N fixers (i.e., legume trees) in the tropics than in mid-/high-latitude ecosystems, our finding indicates that the sensitivity of BNF to N addition is lower in tropical/subtropical forests than in other ecosystems (14.9% vs. 13.9%-37.8%; Figure 2a), which supports a prior observation that humid tropical forests sustained high BNF rates under soil N richness (Reed et al, 2008;Zheng et al, 2018), while many temperate/boreal forests reduced BNF rates after N addition (Gundale et al, 2013;Perakis et al, 2017;Rousk & Michelsen, 2016b;Zackrisson et al, 2004). Given that free-living N fixation is a critical component of terrestrial N input (Reed et al, 2011), our finding indicates that elevated N deposition may reduce free-living N fixation more than symbiotic N fixation, which needs to be considered and integrated into the modeling of terrestrial N budgets in the future (Meyerholt et al, 2016;Wang et al, 2007).…”
Section: Terrestrial Bnf In Response To Nutrient Additionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, we found that symbiotic N fixation was less sensitive to N inputs than was free-living N fixation, as evidenced by the smaller response ratios of BNF in nodule (15.2%) compared to those in soil, litter, moss, and lichen (21.2%-74.1%; Figure 2b). Given that there are more symbiotic N fixers (i.e., legume trees) in the tropics than in mid-/high-latitude ecosystems, our finding indicates that the sensitivity of BNF to N addition is lower in tropical/subtropical forests than in other ecosystems (14.9% vs. 13.9%-37.8%; Figure 2a), which supports a prior observation that humid tropical forests sustained high BNF rates under soil N richness (Reed et al, 2008;Zheng et al, 2018), while many temperate/boreal forests reduced BNF rates after N addition (Gundale et al, 2013;Perakis et al, 2017;Rousk & Michelsen, 2016b;Zackrisson et al, 2004). Given that free-living N fixation is a critical component of terrestrial N input (Reed et al, 2011), our finding indicates that elevated N deposition may reduce free-living N fixation more than symbiotic N fixation, which needs to be considered and integrated into the modeling of terrestrial N budgets in the future (Meyerholt et al, 2016;Wang et al, 2007).…”
Section: Terrestrial Bnf In Response To Nutrient Additionsupporting
confidence: 88%
“…For example, in a Swedish forest, feather mosses exert stronger negative BNF responses to high rates of N addition (50 kg N ha −1 year −1 ) than to low rates of N addition (12.5 kg N ha −1 year −1 ; Gundale et al, 2013). There have been several lines of evidence indicating that fertilization regimes may affect the extent of BNF responses.…”
Section: Factors Affecting the Bnf Response To Nutrient Additionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phyla Cyanobacteria, Planctomycetes, and Verrucomicrobia were positively correlated with the presence of P. juniperinum. Free-living cyanobacteria have been associated with bryophytes in boreal forests of Sweden (66)(67)(68)(69) and can fix atmospheric N, which is then leaked to the moss (69,70). The rates of N fixation in Swedish boreal forests increased with time since fire as moss reestablished, and with it, an increased presence of Cyanobacteria (66).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that light and moisture conditions are more important than N supply in explaining the abundance of V. vitis-idaea (Mäkipää et al 1999;Palmroth et al 2014) and we suggest that the long-term negative response of this species to the N additions is mainly due to tree canopy suppression. For the bryophyte dominating the site, P. schreberi, an immediate negative effect of N addition was expected as bryophytes have a high capacity to take up N, particularly as ammonium and amino acids (Forsum et al 2006;Wiedermann et al 2009), and bryophyte decline in high N environments have been repeatedly reported (Hedwall et al 2010;Verhoeven et al 2011;Gundale et al 2013) and subjected either to direct toxic effects or to increased competition from vascular plants (Turetsky et al 2012 and references therein). Due to the absent immediate effect on bryophyte abundance, it may be that the observed long-term decline of P. schreberi was more related to suppression from competing vegetation than to any immediate toxic effects from the N additions.…”
Section: Discussionmentioning
confidence: 99%